Detection of Herpesviruses (Predominantly HHV-6) in Patients with Guillain–Barré Syndrome - Jéssica Gonçalves Pereira; Tainá Madeira Barros Pontes; Fernanda Martins Maia Carvalho; André Borges Ferreira Gomes; Rafael Santos Erbisti; Ivanildo Pedro de Sousa Junior; Jeová Keny Baima Colares; Danielle Malta Lima; Vanessa Salete de Paula (Biomedicines)
Background/Objectives: Guillain–Barré syndrome (GBS) is a neurological disease that affects the peripheral nerves. The exact cause of this condition is still uncertain, but cross-reactivity between pathogen antigens and nervous tissue may play a crucial role in disease pathogenesis. Roseolovirus humanbeta6 (HHV-6), a neurotropic virus with latency capacity, may be considered a significant candidate for triggering or worsening neurological conditions. In this study, we aimed to investigate the detection of HHV-6 in the CNS from GBS patients. Of the 23 individuals suspected of having GBS, 13 were confirmed as having the disease. We then analyzed the frequency of herpesviruses in the cerebrospinal fluid (CSF) samples from these 13 individuals with GBS who were also tested for enteroviruses and arboviruses and had negative results. Results: After extraction of viral DNA from CSF samples, real-time PCR (qPCR) methodology was used to analyze the frequency and viral load of herpesviruses. Sociodemographic and clinical data were collected for analysis and verification through statistical tests such as Fisher’s exact test and the Mann–Whitney test. Thirteen individuals diagnosed with GBS were tested. Among the 13 patients analyzed, 61.5% were men, 38.4% (5/13) tested positive for HHV-6, 61.5% of the patients tested positive for a herpesvirus, 30.8% had two viral DNAs identified, and one patient presented three different strains. Patients who tested positive for HHV-6 had a significantly longer average length of stay (25.6 days versus 11 days for negative patients). HHV-6 was the most frequent subtype detected in patients positive for herpesviruses (62.5%, 5/8). Discussion/Conclusions: Our results show a possible relationship between HHV-6 and GBS cases despite the small number of patients, raising the question of whether the presence of HHV-6 influences GBS, since its investigation using qPCR is not routinely used. This may have some impact on prognosis, since antiviral therapy is not included in the standard treatment of GBS patients, and viral DNA load may interfere with the inflammatory process of GBS.